Pregnancy‐associated plasma protein A regulates mitosis and is epigenetically silenced in breast cancer. Issue 4 (August 2014) - Loddo, Marco; Andryszkiewicz, Joanna; Rodriguez‐Acebes, Sara; Stoeber, Kai; Jones, Allison; Dafou, Dimitra; Apostolidou, Sophia; Wollenschlaeger, Alex; Widschwendter, Martin; Sainsbury, Richard; Tudzarova, Slavica; Williams, Gareth Haydn
Abstract Aberrant mitosis is a common feature of cancer, yet little is known about the altered genes causing mitotic defects. We screened human tumours for cells with morphological signatures of highly specific mitotic defects previously assigned to candidate genes in a genome‐wide RNA interference screen carried out in HeLa cells (www.mitocheck.org). We discovered a striking enrichment of early mitotic configurations indicative of prophase/prometaphase delay in breast cancer. Promoter methylation analysis of MitoCheck candidate genes assigned to the corresponding 'mitotic delay' class linked this defect to epigenetic silencing of the gene encoding pregnancy‐associated plasma protein‐A (PAPPA), a secreted protease. PAPPA silencing was highly prevalent in precursor lesions and invasive breast cancer. Experimental manipulation of PAPPA protein levels in human mammary epithelial cells and in breast cancer cell lines demonstrates that progression through early mitosis is dependent on PAPPA function, and that breast cancer cells become more invasive after down‐regulation of this protease. PAPPA regulates mitotic progression through modulating the IGF‐1 signalling pathway resulting in activation of the forkhead transcription factor FoxM1, which drives a transcriptional cluster of essential mitotic genes. Our results show that PAPPA has a critical function in normal cell division and is targeted early in breast cancer development. Copyright © 2014 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.